The Effect of Urea Molasses Multi-Nutrient and Medicated Block for Beef Cattle, Beef and Dairy Cow - Suharyono Suharyono; H. Sutanto; Y. Purwanti; Martanti Martanti; A. Agus; U Ristianto (PPIKSN-BATAN, 2014)
Urea molasses multi-nutrient block (UMMB) is a feed supplement and one of the best formulas constructed by the National Nuclear Energy Agency (BATAN). This supplement contains soya bean meal (SBM) and has been developed using different protein sources, such as Enterolobium cyclocarpum (Ec), soya bean waste sauce (SBWs), wheat pollard (WP) and WP bypass protein (WPBp). It has also been developed using medicated block (MB). The objective is to introduce the P-32 tracer for obtaining a new feed supplement, to apply UMMB-SBM on beef cattle for fattening, and to test UMMB-MB on cows in the field. Parameters measured include microbial protein synthesis (MPS) in rumen liquid, daily live weight gain (DLWG), milk production and total count of worm in feces. Statistical analysis used were Latin squares, Student’s t-test, and completely randomized design. The UMMB-SBM was better than UMMB-Ec, UMMB-SBWs, and UMMB-WP, because it was able to increase MPS by up to 205.67%, superior to the other feed supplements (51.01%, 34.04%, and 73.94% respectively). On the other hand, with UMMB-WPBp supplementation, MPS was enhanced by 425.27%. The UMMB-SBM was able to increase DLWG by 0.34, 0.30, 0.38 and 0.36 kg/(animal d) on Bali cattle, Ongole, Simmental, and Frisian Holstein cross breed respectively. The increase of cost benefit ratio was affected by increasing DLWG. These values were 1:1.89; 1: 1.34; 1:1.45 and 1:1.35 respectively. UMMB-MB-C. aeruginosa and albendazole increased milk production by 4.23% and 46.56% respectively. In the first communal group, beef cows that received UMMB-MB albendazole were able to increase feed consumption, including dry matter, organic matter, crude protein, and total digestible nutrient, at P<0.05.The second communal group, feed consumption significantly differed from control at P<0.05 on crude protein, and total digestible nutrient. UMMB-MB tends to be effective only for ten days on the total amount of egg worm in feces.Received: 28 January 2014; Revised: 13 June 2014; Accepted: 23 June 2014